The Rhetorical argumentation: Applied and Concept - Dawood Abdulhassan, Adnan (Al-Adab Journal, 2020)
Argumentation considers a cultural concept that moves in a systematic bond of the speaker and the audient surrounding environment, and that what demand renewing the concept and regulate its techniques.This research had bind (The rhetorical argumentation) at (Perelma and Tytica) as applied or as a concept in a poetic text to allocate the argumentative features in it. It is obvious that a poetic texts have privileged efficacious nature which contribute effectively in allocating the kinds of (Rhetorical argumentation) techniques.